PERAN MUSIK TUDDUKAT DALAM RITUAL ARAT SABULUNGAN DI KABUPATEN MENTAWAI - Ruth Meliani Tatubeket; Agustina Agustina; Agusti Efi (Program Studi Sosiologi Agama Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2019)
Tuddukat is traditional music of Mentawai people.,consist of three drums from wood, Ina (the biggerTuddukat ), Sileleite (midle of tuddukat), and Toga(Small tuddukat). Tuddukat used by mentawai peoplefor expressing their feeling, such us sad, happy, sorrow,in differance occassion. In used, tuddukat is a mediumof communication among people and their own Gods(Taeka). In other hand, tuddukat performed in specialoccasion, deal with the desires of mentawai people willcommunicating with other or Taeka, it presenting bySikerei (a person as medium to talk to Gods). Finaly,Tuddukat is media communitation among two dimensi,seen and unseen worldsKeywords: Tuddukat, seen and unseen worlds, Taeka